Thismiadomei and T.terengganuensis (Thismiaceae), two new species, and T.javanica, a new record from Terengganu, Peninsular Malaysia - Yunoh, Siti-Munirah Mat (PhytoKeys, 2019)
Abstract. Two new species of the mycoheterotrophic genus Thismia Griff. (Thismiaceae), Thismiadomei Siti-Munirah and T.terengganuensis Siti-Munirah from Peninsular Malaysia, are described and illustrated. Thismiadomei, characterized by its perianth lobes that are upright and curve inward, but are imperfectly connate, falls within sectionOdoardoa. Thismiaterengganuensis is characterized by its mitre with three appendages on its apex, so falls within sectionGeomitra. Both new species are unique and totally different from other described species, T.domei by the trichomes on its outer perianth tube surface and T.terengganuensis by its mitre with slender appendages. Thismiajavanica J.J.Sm, also from Terengganu, is a new record for Peninsular Malaysia.